A concept design of a motorbike with 3D model - Omari, Mhd Yaser (Kuliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2009)
Although motorbikes are used widely in Malaysia there isn't a published ergonomic and anthropometric studies concerning the Malaysian body user also the motorbikes designs need to be more friendly, in our study we present ergonomic and anthropometric survey and experiment which is concerning the Malaysian user the data was firstly gathered through a questionnaire which invests the uncomfortable positions for the Malaysian motorbike drivers and their aesthetic tends about design its form shape volume and colour as an elements of the new concept for the motorbike design according to their three different ethnicities Malay Chinese and Indian. Also an experimental trail was used to choose the best position of measurements for the Malaysian, and after collecting the mentioned data it would be analysed to get the result which is considered the final 3d model. These results were used to build the prototype with industrial clay.